2011
DOI: 10.1111/j.1540-5826.2011.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Science for All: Engaging Students with Special Needs in and About Science

Abstract: The notion of "science for all" suggests that all students-irrespective of achievement and ability-should engage in opportunities to understand the practice and discourse of science. Improving scientific literacy is an intrinsic goal of science education, yet current instructional practices may not effectively support all students, in particular, students with special needs. Argument-based inquiry approaches, such as the Science Writing Heuristic (SWH), require all students to construct their scientific unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 51 publications
1
30
0
1
Order By: Relevance
“…This scenario is not unusual, as textbooks play a dominant role in STEM instruction (Brigham, Scruggs, & Mastropieri, 2011). Unfortunately for the struggling learner, the same unknown science-specific language conventions and vocabulary terms that affect learning during oral lectures can restrict ability to read and comprehend textbooks and other text-based materials (Villanueva & Hand, 2011). As a result, the inability to comprehend text or keep pace during face-to-face instruction results in a perpetual cycle of failure within STEM and other secondary-level content coursework for many struggling students.…”
Section: Identifying Mismatches: Instructional Methods and Content Dementioning
confidence: 99%
“…This scenario is not unusual, as textbooks play a dominant role in STEM instruction (Brigham, Scruggs, & Mastropieri, 2011). Unfortunately for the struggling learner, the same unknown science-specific language conventions and vocabulary terms that affect learning during oral lectures can restrict ability to read and comprehend textbooks and other text-based materials (Villanueva & Hand, 2011). As a result, the inability to comprehend text or keep pace during face-to-face instruction results in a perpetual cycle of failure within STEM and other secondary-level content coursework for many struggling students.…”
Section: Identifying Mismatches: Instructional Methods and Content Dementioning
confidence: 99%
“…Implementing the argument-based inquiry approaches may be influential in closing the achievement gap by embedding writing and argumentation within the science inquiry activity (Grimberg & Hand, 2009, Cavagnetto, 2010. In order to achieve equitable learning for all, instruction have to values and respect students' experience and prior knowledge, provide adequate support and resource, and create non-threatening environment (Villanueva & Hand, 2011). While researchers focus on closing achievement gaps by gender, ethnicity, and socioeconomic status, Villanueva, Taylor, Therrien, and Hand (2012) also suggested that student success was also greatly increased for students who have difficulty with reading and writing skills using the inquiry.…”
Section: An Analysis Of Students' Science Iowa Test Of Educational Dementioning
confidence: 99%
“…Students need to acquire essential factual and conceptual science knowledge to make meaningful connections with the natural world (Palincsar, Magnusson, Collins, & Cutter, 2001;Powell & Arum, 2007). As students gain a better understanding of science, they can make more informed decisions, on personal and civic levels, when dealing with societal issues (Hazen & Trevil, 2009;Villanueva & Hand, 2011;Yore, 2012). For example, students who have gained background knowledge related to topics such as ecology, pollution, natural resources, and the use of energy are more likely to make decisions that positively impact the quality of their environment and improve human existence.…”
Section: Why Is Science Learning Important For Students?mentioning
confidence: 99%
“…However, improving science achievement for students in some subgroups (e.g. students with learning disabilities) has proven to be largely unsuccessful (Villanueva & Hand, 2011), which puts students in these subgroup populations at greater risk for failure (Therrien, Hughes, & Hand, 2011).…”
Section: Science Learning For All Studentsmentioning
confidence: 99%
See 1 more Smart Citation